Cardiovascular Adverse Events Associated with Monoclonal Antibody Products in Patients with COVID-19 - Jingrui Zou; Fuyuan Jing (MDPI AG, 2022)
Little is known about cardiovascular safety profiles for monoclonal antibody products that received the FDA Emergency Use Authorization for COVID-19. In this study, data from the FDA Adverse Event Reporting System from the first quarter of 2020 to the second quarter of 2022 were used to investigate cardiovascular safety signals associated with seven monoclonal antibody products (casirivimab + imdevimab, bamlanivimab, bamlanivimab + etesevimab, sotrovimab, tocilizumab, bebtelovimab, tixagevimab + cilgavimab) in COVID-19 patients. Disproportionality analyses were conducted using reporting odds ratio and information component to identify safety signals. About 10% of adverse events in COVID-19 patients were cardiovascular adverse events. Four monoclonal antibody products (casirivimab + imdevimab, bamlanivimab, bamlanivimab + etesevimab, and bebtelovimab) were associated with higher reporting of hypertension. Tocilizumab was associated with higher reporting of cardiac failure and embolic and thrombotic event. Casirivimab + imdevimab and bamlanivimab were also associated with higher reporting of ischemic heart disease. No cardiovascular safety signals were identified for sotrovimab and tixagevimab + cilgavimab. The results indicate differential cardiovascular safety profiles in monoclonal antibodies. Careful monitoring of cardiovascular events may be considered for certain COVID-19 patients at risk when they are treated with monoclonal antibodies.